PENERAPAN METODE DEMONSTRASI DALAM MENIGKATKAN KEMAMPUAN BERWUDHU PADA KELOMPOK B3 TK ISLAM YLPI MARPOYAN - Aulia Akmal (Generasi Emas: Jurnal Pendidikan Islam Anak Usia Dini, 2018)
A demonstration method is a way of learning by demonstrating or demonstrating something in front of a student, conducted inside or outside the classroom, by showing how the process of something is happening. Methods of demonstration can be carried out in various ways by grouping students into groups with 3-4 members in each group, then the teacher preparing a place to perform ablution practice, giving freedom to any group who wish to advance to practice first and let them perform ablution as good as they can be. Until finally they know how to perform a proper wudoo according to Islamic teachings. This research is a Classroom Action Research (PTK) that is research based on problems that arise in learning activities. Subjects in this study were students of B3 TK Islam YLPI Marpoyan group with 15 children with details of men 8 people and 7 women with average age 5 years. The result of observation and analysis on the implementation of learning activities can be concluded that the activities of wudoo development on group B3 using demonstration method has been successful and there is improvement. Students are able to independently in practicing the ablution movement so that the teacher is more role as monitoring in learning ablution material.